La creación colectiva como estrategia pedagógica para la creación de competencias artísticas (2018)
This document is the proposal made during the research teaching practice in the La Amistad District School, where with the group of students who belong to the emphasis “Learning through art”, where as a mandatory and fundamental area (General Law of Education, Art. 23), their competencies will be evaluated, through the final assembly, since, in this area, if the work does not circulate, it is not evaluated, since the state tests are not contemplated by us